2016
DOI: 10.1186/s12889-016-3364-7
|View full text |Cite
|
Sign up to set email alerts
|

Socioecological factors influencing women’s HIV risk in the United States: qualitative findings from the women’s HIV SeroIncidence study (HPTN 064)

Abstract: BackgroundWe sought to understand the multilevel syndemic factors that are concurrently contributing to the HIV epidemic among women living in the US. We specifically examined community, network, dyadic, and individual factors to explain HIV vulnerability within a socioecological framework.MethodsWe gathered qualitative data (120 interviews and 31 focus groups) from a subset of women ages 18–44 years (N = 2,099) enrolled in the HPTN 064 HIV seroincidence estimation study across 10 US communities. We analyzed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 83 publications
2
44
1
1
Order By: Relevance
“…The incidence of HIV in the United States (U.S.) has remained stable in the past few years and HIV diagnoses among women have been in decline [1]. However, certain subpopulations of women (e.g., women of color, women with low income or low education, and women who inject drugs) are still at considerable risk for HIV [2]. Research on social and structural forces that increase vulnerability for HIV and other sexually transmitted infections (STIs) among women has demonstrated that a multitude of factors, including minority status, low socioeconomic status (SES), and adverse experiences, intersect to create milieus of risk where women, especially women of color, are at a disadvantage when it comes to avoiding HIV and STI [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of HIV in the United States (U.S.) has remained stable in the past few years and HIV diagnoses among women have been in decline [1]. However, certain subpopulations of women (e.g., women of color, women with low income or low education, and women who inject drugs) are still at considerable risk for HIV [2]. Research on social and structural forces that increase vulnerability for HIV and other sexually transmitted infections (STIs) among women has demonstrated that a multitude of factors, including minority status, low socioeconomic status (SES), and adverse experiences, intersect to create milieus of risk where women, especially women of color, are at a disadvantage when it comes to avoiding HIV and STI [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Other factors identified were food insecurity, partner age >35, intimate partner violence (IPV), partner's sexual concurrency with multiple women, prevalence of substance abuse, and sex exchange for financial and in-kind resources in their communities. 30 …”
Section: Resultsmentioning
confidence: 99%
“…The distribution of asymptomatic sexually transmitted infections varies worldwide, and studies have shown that social, economic and behavioral conditions influence their epidemiology [ 4 , 5 ]. Therefore, in general, higher prevalences of HIV, syphilis, and hepatitis B and C have been found in low- and middle-income countries compared to developed countries [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%